Estudo morfológico da blenda polimérica poli(metacrilato de metila)/poli(tereftalato de etileno) reciclado (PMMA/PET) - Dantas, Rosanne de Lima Filgueira (2011)
Among the options for plastics modification more convenient, both from a technical-scientific and economic, is the development of polymer blends by processing in the molten state. This work was divide into two stages, with the aim to study the phase morphology of binary blend PMMA / PET blend and this compatibilized by the addition of the poly(methyl methacrylate-co-glycidyl methacrylate-co-ethyl acrylate) copolymer (MMA-GMA-EA). In the first stage is analyzed the morphology of the blend at a preliminary stage where we used the bottle-grade PET in a Haake torque rheometer and the effect of compatibilizer in this blend was evaluated. In the second stage the blend was processed using the recycled PET in a single screw extruder and subsequently injection molding in the shape of specimens for mechanical tests. In both stages we used a transmission electron microscopy (TEM) to observe the morphologies of the samples and an image analyzer to characterize them. In the second stage, as well as analysis by TEM, tensile test, scanning electron microscopy (SEM) and atomic force microscopy (AFM) was performed to correlate the morphology with the mechanical properties. The samples used in morphological analyzes were sliced by cryo-ultramicrotomy technique for the analysis by TEM and the analysis by SEM and AFM, we used the flat face of the block after cut cryogenic. It was found that the size of the dispersed phase decreased with the addition of MMA-GMA-EA in blends prepared in a Haake. In the tensile test, the values of maximum tensile strength and modulus of elasticity is maintained in a range between the value of pure PMMA the pure PET, while the elongation at break was influenced by the composition by weight of the PMMA mixture. The coupling agent corroborated the results presented in the blend PMMA / PETrec / MMA-GMA-EA (80/15/5 %w/w), obtained by TEM, AFM and SEM. It was concluded that the techniques used had a good morphologic correlation, and can be confirmed for final analysis of the morphological characteristics of the blends PMMA / PET